Work ,wages And wellbeing Of Agricultural Labourers In Palghat District - Sankar PN (Department of Agricultural Economics, College of Horticulture, 1985)
The study was undertaken to understand the socio-economic conditions of agricultural labourers in Palghat district. The specific objectives of the study were 1. To study the level of education of agricultural labourers 2. To understand the extent of employment, under employment and unemployment 3. To study the wage rates and mode of payment of wages 4. To assess the level of income, expenditure, levels of living, savings, indebtedness and other aspects such as health, hygiene, aspirations, etc. Alathur and Chittur Blocks which are having the highest percentage of agricultural labourers in the district were selected for the study. One hundred agricultural labour households were selected from four villages belonging to two Panchayaths each from a Block, adopting a three stage random sampling. Unlike other parts of the country where the majority of agricultural labourers belonged to scheduled castes, only 23 per cent of the selected households belonged to scheduled castes. Seventy three per cent belonged to Ezhava and the rest to Muslim communities. The sex ratio worked out for the sample as a whole was 992 which was quite contradictory to the pattern for the district as well as the State. The average family size for the sample as a whole was found to be 5. The lowest income group had the lowest family size and the highest income group had the highest family size. It was found that 55.2 per cent of the population in the selected households constituted the potential labour force but only 49.4 per cent constituted the actual working labour force. The percentage of literacy of members in the age groups of six years and above was 52.01 which was below that of the district as well as the State. The per-centage of literacy of females was less than males at all levels of education. For the sample as a whole the average number of earners worked out as 2.47 and the dependency ratio was 1.02. Average annual employment per household for the sample as a whole was found to be 170.65 man days of which 77.5 per cent was in agriculture. The average annual employment per worker was found to be 79.45 man days which was very low. The severe drought which affected the crop during the reference period, large scale use of tractors, fragmentation of land, use of high yielding varieties, labour saving tactics of farmers, etc. were the possible reasons identified for the low level of employment per person. The months of Karkkitakam and Chingam were identified as the lean months and the months Edavam, Kanni and Tulam were identified as peak months as far as employment in agriculture is concerned. Nearly 80 per cent of the workers received employment for less than 120 days which indicated that the bulk of the workers remained unemployed for about 8 months in a year. It was also found that none of the workers was fully employed; 1.4 per cent of them was moderstely under employed, 98.6 per cent was severely under employed. The average level of under employment for the sample as a whole was 66.37 per cent of the total available man days. Under employment per man unit was 66.41 per cent of the total available man days per man unit. It was also found that 10.51 per cent of the potential labour force was unemployed. The wage rates of labourers ranged from Rs.10/- to Rs.15/- in the case of males and Rs.5/- to Rs.7/- in the case of females for employment in agriculture. Fon non-agricultural workers the rates ranged from Rs.10/- to Rs.20/- for males and Rs.5/- to Rs.8/- for females. There was striking wage differentials between men and women in both agricultural and non-agricultural employment. Payments made in kind ranged from 6 to 10 edangazhis of paddy for male and 5 to 8 edangazhis of paddy for females. Harvesting is paid exclusively in kind and the share of the land lord and the labourer ranged from 7: 1 to 6: 1. It was observed that the increase in the real wages of agricultural labourers during the period from 1971-72 to 1981-82 was only marginal. For the sample as a whole roughly 80 per cent of the total income accrued from wage employment; 57 per cent from agricultural and 14 per cent from non-agricultural employment. The rest was from other sources. The average per capita annual income for the sample as a whole was Rs.472.39. The per capita per day income was found to be Rs.1.29 and per day income per adult consumption unit was Rs.1.52. It was also observed that there was inequality in the distribution of income. On an average the households spent Rs.2925.78 annually of which 62.2 per cent was on food items. It was found that as income increased the proportion of total expenditure on food increased at first and then started declining. No correlation was observed in the case of non-food items to changes in income. The per capita per day consumption expenditure ranged from Rs.1.25 to Rs.2.01, the average for the sample as a whole being Rs.1.54. The consumption expenditure per day per consumption unit was Rs.1.82 for the sample as a whole. It was also found that all the households in sample were below poverty line. The per household income was found to be insufficient to meet the per household consumption expenditure in any of the income groups except in income group I5. Negative saving was noticed in 94 per cent of the households. The deficit per household for the sample as a whole was Rs.503.05. On an average for the sample as a whole indebtedness per family and per capita were found to be Rs.832.30 and Rs.166.45 respectively. Indebtedness per household or per capita did not show any correlation to changes in the per household income. The highest percentage of indebtedness was found to be incurred for meeting consumption expenses followed by social and religious functions. Ninety eight per cent of the houses of the labourers was found to be kutcha ones. Seventy two per cent was tiled and the rest thatched. On an average the number of rooms available per household was 2.62. It was found that all the selected households had accessibility to hospitals at distance ranging from less than 1 km to more than 2 km. Only two per cent of the households had their own source of drinking water and the rest had to depend on public taps, public or private wells and tanks. Similarly only 2 per cent of households had latrines. The number of man days lost due to disesees per family was found to be 4.44. Only the days lost during peak seasons were taken into account. It was observed that 77 per cent of the respondents preferred to have a days rest during a week. With regard to the educational aspirations of respondents for their children the majority of them desired high school education for their sons and daughters. As far as occupational aspirations are concerned 40.58 per cent desired government service for their sons while 37.68 per cent had no definite opinion. For female children 39.59 per cent aspired government service while 52.08 per cent had no definite opinion. It was found that 71 per cent of the respondents had membership in trade union organisations. The Kerala State Karshaka Thozhilali Union was found to be the most powerful trade union organisation absorbing 69 per cent of the respondents as its members.